Routledge philosophy guidebook to Hume on knowledge - Noonan, Harold W. (London, Routledge, 1999)
"David Hume (1711-76) is one of the greatest figures in the history of British philosophy. Of all of Hume's writings, the philosophically most profound is undoubtedly his first, A Treatise of Human Nature. Of the three books that make up the Treatise, the first, in which he outlines the epistemology and metaphysics underpinning his system, is universally acknowledged to be his greatest intellectual achievement."--BOOK JACKET. "Hume on Knowledge thus provides us with a map to Book 1 of the Treatise and sets out its principal ideas and arguments in a clear and readable way. This book will enable any reader coming to the Treatise for the first time easily to understand the importance of and intricacies inherent in Hume's thought."--BOOK JACKET
Includes bibliographical references (p. 213-216) and index
Keywords: Hume, David, -- 1711-1776.; Knowledge, Theory of; Philosophy of mind